IMPROVING STUDENTS' SPEAKING SKILLS MOTIVATION USING YOUTUBE VIDEO AND ROLE PLAY - Daru Susanti,; Edri,; Arman Syah Putra,; Nurhayati,; Zikriah,; Nurul Aisyah, (JOEL: Journal of Educational and Language Research, 2022)
The objectives of this study are improving the students speaking motivation at Tourism Academy Jakarta, the application of YouTube video role play for improving students’ speaking motivation at Tourism Academy Jakarta also the research question is the students’ perceptions of the use of You Tube and Role Play. The action research is condected in one class with 15 students at semester one. This researcher was conducted on 7 March November 2017 until September, 14th, 2018 located in Akademi Pariwsata Jakarta. The researcher used several instrument to collect the data. The other data were obtained from observation, speaking test, interview and questioner The interview was done to 15 students of semester one of Tourism Academy Jakarta and an English teacher ( male and female). The method of this research was planning, acting, observation, reflection in three cycles.The first finding of the first objective was the progress of students’ speaking score and motivation questioner data had increased in each cycles. The students’ interview had a positive result. The second finding of teaching and learning by using You Tube and role play had been successfully increasing the students’ motivation and confidence in speaking. The results of this research shown that the use of Role Playing technique was successful to improve the students’ speaking ability. They found that this teaching can improve speaking’s motivation and skill effectively